Etiologies of apnea of infancy. Issue 6 (14th April 2020) - Ginsburg, Daniella; Maken, Kanwaljeet; Deming, Douglas; Welch, Mark; Fargo, Ramiz; Kaur, Prabhleen; Terry, Michael; Tinsley, Larry; Ischander, Mariam
Abstract: Background: To date there are limited data in the literature to guide the initial evaluation for etiologies of apnea in full‐term infants born at greater than or equal to 37 weeks conceptional age (apnea of infancy [AOI]). Pediatricians and pediatric pulmonologists are left to pursue a broad, rather than targeted and a stepwise approach to begin diagnostic evaluation. Methods: We performed a retrospective chart review of 101 symptomatic full‐term infants (age under 12 months) diagnosed with apnea with an inpatient multichannel pneumogram (six channels) or a fully attended overnight pediatric polysomnogram in our outpatient sleep center accredited by American Academy of Sleep Medicine (AASM), scored using the standards set forth by the AASM. The infant was diagnosed as having AOI if the apnea hypopnea index (AHI) was greater than 1 (AHI is defined as the number of apnea and hypopnea events per hour of sleep). The final diagnosis/etiology was determined based on physician clinical assessment and work up. We then determined the frequency for each diagnosis. Results: We found that the three most common etiologies were gastroesophageal reflux disease (GERD) (48/101), upper airway abnormalities/obstruction (37/101), and neurological diseases (19/101). There were significant numbers of infants with multiple etiologies for AOI. Conclusion: Based on the frequencies obtained, pediatric practitioners caring for full‐term infants with apnea of unknown etiology are advised to begin with evaluation of more likely causes such as GERD and upper airway abnormalities/obstruction before evaluating for less common causes.